Emodin and Aloe-Emodin Suppress Breast Cancer Cell Proliferation through ERα Inhibition - Pao-Hsuan Huang (Evidence-Based Complementary and Alternative Medicine, 2013)
The anthraquinones emodin and aloe-emodin are abundant in rhubarb. Several lines of evidence indicate that emodin and aloe-emodin have estrogenic activity as phytoestrogens. However, their effects on estrogen receptor α (ERα) activation and breast cancer cell growth remain controversial. The goal of this study is to investigate the effects and molecular mechanisms of emodin and aloe-emodin on breast cancer cell proliferation. Our results indicate that both emodin and aloe-emodin are capable of inhibiting breast cancer cell proliferation by downregulating ERα protein levels, thereby suppressing ERα transcriptional activation. Furthermore, aloe-emodin treatment led to the dissociation of heat shock protein 90 (HSP90) and ERα and increased ERα ubiquitination. Although emodin had similar effects to aloe-emodin, it was not capable of promoting HSP90/ERα dissociation and ERα ubiquitination. Protein fractionation results suggest that aloe-emodin tended to induce cytosolic ERα degradation. Although emodin might induce cytosolic ERα degradation, it primarily affected nuclear ERα distribution similar to the action of estrogen when protein degradation was blocked. In conclusion, our data demonstrate that emodin and aloe-emodin specifically suppress breast cancer cell proliferation by targeting ERα protein stability through distinct mechanisms. These findings suggest a possible application of anthraquinones in preventing or treating breast cancer in the future.